Engaged by the "Big Show" Now,' Harper's Weekly caricature, 1907 - W. A. Rogers (1854-1931)::::::::: (Harper & Brothers, 1907)
Issue of 'Harper's Weekly, A Journal of Civilization' (Volume LI (volume 51), no. 2653) political magazine featuring caricatures of William Randolph Hearst dressed as a circus clown while holding an 'Ind. League Inc.' labeled balloon. Hearst is also leading away a circus elephant representing the N.Y.G.O.P. (New York Republican Party). In the background, President Theodore Roosevelt sits on horseback while aiming a rifle at a third term after hitting the first term and second term targets. Text beneath the cartoon reads "Engaged by the "Big Show" Now". The reverse side hosts commentaries. Circa October 26th, 1907.